Juozas Stoukus (1886–1946) mathematical work - Kastickaitė, Joana (Lietuvos matematikos rinkinys, 2011)
Juozas Stoukus (1886–1946) was an educator, a mathematician, the author of the textbooks. He wrote the following books: “Analizinės geometrijos pagrindai” (Basics of Analytic Geometry), “Begalinių mažybių analizio pagrindai” (Basics of Infinitesimal Variable Analysis), “Aritmetikos uždavinynas” (Book of Problems in Arithmetic), 1, 2 parts, “Geometrijos uždavinynas” (Book of Problems in Geometry), 1, 2 parts.